JASNOŚĆ PRAWA PODATKOWEGO JAKO WARUNEK POPRAWNEJ LEGISLACJI PODATKOWEJ - Mączyński, Dominik; Sowiński, Ryszard (Wydział Prawa i Administracji UAM, 2005)
Tax law interferes into the sphere of citizens’ property rights. Therefore it is of extreme importance that during the tax legislation process the (legal) principles developed on the basis of law, legal science and jurisdiction have been obeyed. The starting point for our considerations is a statement that tax provisions should be formulated in a way allowing reconstruction of legal norms precisely formulated therein. In the paper, provisions related to the creation of law are analysed, with particular attention drawn to the regulations applying to tax law. Further, the rich jurisdiction of the Constitutional Tribunal, whose verdicts have on many occasions given rise to a number of detailed postulates deriving from general constitutional principles of the legislative process, is presented. The Tribunal often emphasised that legal regulations must be clear, precise and comprehensible. Similar postulates are frequently found in the jurisdiction of administrative courts which have often expressed an opinion that the in dubiopro tributario principle should govern the interpretation of tax law. According to that principle, no tax obligations should be imposed if their legal grounds are imprecise or incomprehensible. If this principle is consistently applied, the legislator will be bound to a stricter discipline in the legislative process of tax law. The present paper is meant to be another voice in the wide discussion that has been going on in the field of financial law.
TRANSPARENCY OF TAX LAW AS A PREREQUISITE FOR PROPER TAX LEGISLATION